Research recast(ed): S3E15 - Creative chemists on creating a cleaner, greener future for everyone - Leschyshyn, Brooklyn; Smadis, Natalie; Lee, Roland; Mundle, Trevor (My University, 2024)
On today’s episode we had the pleasure of being joined by Dr. Roland Lee and Trevor Mundle. The two test our preconceived notion of the truth behind environmentally friendly products. Dr. Roland Lee and Trevor Mundle collaborate between the MacEwan lab and Green Tech, bringing together experts in chemistry, finance, investment, and sustainable practices. They use cutting-edge pyrolysis technology to convert various feedstocks into valuable products, which reduces emissions, fossil fuel dependencies, water usage, and landfill needs. Their objective is to transform waste streams into valuable resources.
Keywords: green chemistry; waste management